2005
DOI: 10.1007/s10038-005-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 status in the Thai population

Abstract: Human serum paraoxonase 1 (PON1), a highdensity lipoprotein (HDL)-associated enzyme, has been shown to reduce the oxidation of low-density lipoprotein (LDL) and HDL by degrading lipid peroxides. This property of PON1 accounts for its ability to protect against atherosclerosis. In this study, we identified four polymorphisms in both the coding (L55M and Q192R) and regulatory regions (T-108C and G-909C) of the human PON1 gene in 202 healthy Thai individuals and investigated the influence of these polymorphisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 53 publications
(93 reference statements)
5
19
1
2
Order By: Relevance
“…This enzyme has two distinct activities, i.e., paraoxonase and arylesterase and each of these activities reflects a unique genotype [Furlong et al 1988;Gaidukov et al 2006;Phuntuwate et al 2005]. In accordance with the data above, we can conclude that the BB phenotype is not affected by the QQ, QR, or RR genotypes.…”
Section: Pon1 Genotypessupporting
confidence: 73%
“…This enzyme has two distinct activities, i.e., paraoxonase and arylesterase and each of these activities reflects a unique genotype [Furlong et al 1988;Gaidukov et al 2006;Phuntuwate et al 2005]. In accordance with the data above, we can conclude that the BB phenotype is not affected by the QQ, QR, or RR genotypes.…”
Section: Pon1 Genotypessupporting
confidence: 73%
“…39,[54][55][56][57] In this study, a wide variation in PON1 activity among individuals was observed; a variability of 6.17-fold was observed when phenylacetate was used as a substrate, and a 4.4-fold variability was observed with substrate CMPA. Although a large interindividual variation in PON1 activity was observed in this work, there is actually less variation in this indigenous population compared with others.…”
Section: Phenotype and Genotype Of Pon1mentioning
confidence: 84%
“…Our results agree with previous studies that reveal interpopulation differences in allele frequencies for the PON1 polymorphisms, and support the hypothesis that indigenous Amerindians and Asians share a common ancestral origin, perhaps the reason why populations from America and Asia demonstrate strong genetic affinities. 37,[55][56][57]63 Given the role of PON1 in pesticide toxicity, 64 it is not surprising that particular attention has been devoted to factors that may modulate PON1 activity or expression. 10,67,68 An individual's plasma PON1 activity toward a particular substrate can be predicted by PON1 polymorphisms in both the coding and regulatory regions, 64,32 and may also be modulated by environmental factors including pes- 26,36,55,63 Our finding that no significant variation in AREase activity was associated with specific PON1 M155L or Q192R polymorphisms was in agreement with previous studies.…”
Section: Phenotype and Genotype Of Pon1mentioning
confidence: 99%
“…The PON1 activity was determined using paraoxon (diethyl p-nitrophenyl phosphate) and phenyl acetate (Phuntuwate et al 2005). Paraoxon hydrolytic activity was measured by a continuous spectrophotometer at 405 nm at 25°C for 3 min and expressed as nmol of 4-nitrophenol formed per minute per ml (nmol/min/ ml).…”
Section: Methodsmentioning
confidence: 99%